A facile method for classifying starch fractions rich in long linear dextrin. (February 2023) - Chi, Chengdeng; Zhou, Youcai; Chen, Bilian; He, Yongjin; Zhao, Yingting
Abstract: Fractionation of linear dextrins with different chain lengths was of great significance for the preparation of functional foods. Traditional gradient non-solvent precipitation method for the fractionation was time-consuming and labor-intensive, making it inconvenient for large-scale dextrin fractionation. The aim of this study was to establish a novel method to fractionate long linear dextrins from debranched waxy maize starch by simply heating (70–80 °C) and centrifuging the debranched starch solution. The results showed that the linear dextrins produced during the debranching process formed ordered structures with melting temperature of 58.8–95.4 °C. According to the analysis of starch thermostability and chain length distribution, it was found that thermostability of ordered structure was significantly and positively correlated with the chain length of linear dextrins. During heating at 70 and 80 °C, less ordered structures with weak thermostability were melted in solution, herein short linear dextrins were removed from debranched starch via centrifugation and thermostable ordered structures could be fractionated to obtain long linear dextrins. By this simple "heating-centrifugation" method, the content of long linear dextrins in starches was increased from 27.08% to 43.40%. This study provided a promising pathway to fractionate long linear dextrins. Graphical abstract: Image 1 Highlights: A method for isolating long linear dextrin from debranched starch was established. Ordered structure packed with long linear dextrin (LD) had high thermostability. Ordered structure was fractionated to obtain long LD by heating and centrifugation. Long LD content in starch was increased from 27.08% to 43.40% after the treatment. Short LD with polymerization units of 13–24 formed helical structure rapidly.